Amorphous inorganic ion conductor, preparation method and application
By using lithium tetrachloroaluminate and sodium tetrachloroaluminate as interface phase in solid lithium metal batteries, the problem of uneven ion transmission between the positive electrode and the solid electrolyte is solved, and the problem of uneven ion transmission between the positive electrode and the solid electrolyte is improved. Lithium ion migration rate and battery performance reduce preparation temperature and cost.
Patent Information
- Application Number
- CN202411235064.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-01-03
AI Technical Summary
In solid lithium metal batteries, the ion transmission between the interface between the positive electrode and the solid electrolyte is uneven, resulting in low lithium ion migration rate and depth, large battery polarization, small utilization of active materials, and high-temperature sintering aids trigger elements interdiffusion, hindering lithium ions. migrate.
The amorphous inorganic lithium ion conductor LixNa1-xAlCl4 is prepared by mixing lithium tetrachloroaluminate and sodium tetrachloroaluminate. It is used as the interface phase between the positive electrode and the solid electrolyte. It forms an amorphous structure through melting and cooling to enhance lithium ion migration The rate is reduced by heat treatment and hot pressing curing, and element diffusion is inhibited.
It significantly improves the lithium ion migration rate, reduces battery polarization, improves rate performance, extends battery life, and reduces preparation temperature and cost, making it suitable for industrial applications.
Smart Images

Figure CN119240766A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid-state lithium metal batteries, and more specifically, relates to an amorphous inorganic ion conductor, a preparation method and an application thereof. Background Art
[0002] Solid-state lithium metal batteries have become a research hotspot in the field of electrochemical energy storage in recent years due to their high energy density and safety. The solid electrolyte of solid-state lithium metal batteries exhibits high ionic conductivity, wide electrochemical window and excellent reduction stability. However, there are problems such as uneven ion transport, low migration rate and depth at the solid electrolyte / electrode interface, which lead to large battery polarization and low utilization of active materials. Current research mainly focuses on improving the stability of the solid electrolyte / lithium negative electrode interface.
[0003] In fact, compared with the deformable lithium negative electrode, the interface wettability between the rigid positive electrode particles and the solid electrolyte is worse, resulting in uneven ion transfer, thereby reducing the charge transfer rate and battery capacity. In addition, the presence of a large number of pores between the particles also reduces the lithium ion migration rate, so the reaction kinetics is weakened, the internal resistance of the battery increases, and the rate performance is poor (<0.1C). At the same time, during the cycle, the volume change of the positive electrode will induce stress / strain at the interface, resulting in a decrease in the reactive area and active material utilization, accelerating capacity decay, and reducing battery life (<50 cycles).
[0004] Although hot pressing and sintering the cathode particles and solid electrolyte can improve the cathode ion migration rate and depth to a certain extent, at high temperatures (>1000°C), interdiffusion of elements usually occurs between the cathode material and the solid electrolyte, forming an impurity phase, which in turn hinders lithium ion migration. Introducing sintering aids as interface phases, such as Li3BO3 and LiBO2, can reduce the cathode sintering temperature and inhibit interdiffusion of elements. However, the ionic conductivity of such interface phases is usually low (<10 -6 S cm -1 ), resulting in slow interfacial ion conduction, large battery polarization and poor rate performance (<0.2C). Summary of the invention
[0005] In view of the above defects or improvement needs of the prior art, the present invention provides an amorphous inorganic ion conductor, a preparation method and an application thereof, the purpose of which is to improve the migration rate of lithium ions.
[0006] To achieve the above object, according to a first aspect of the present invention, a method for preparing an amorphous inorganic ion conductor is provided, comprising:
[0007] Mixing lithium tetrachloroaluminate and sodium tetrachloroaluminate uniformly to obtain a mixture;
[0008] The mixture is melted to obtain a molten precursor, and after cooling to room temperature, an amorphous inorganic lithium ion conductor Li x Na 1-x AlCl4, 0.15≤x≤0.85;
[0009] Wherein, the amorphous inorganic lithium ion conductor Li x Na 1-x AlCl4 is used as the interfacial phase between the positive electrode and the solid electrolyte in solid-state lithium metal batteries.
[0010] Further, 0.55≤x≤0.85.
[0011] Further, x=0.55.
[0012] Further, melting the mixture to obtain a molten precursor comprises:
[0013] Under a protective atmosphere, the mixture is heated at a heating rate of 10 to 20° C. / min to melt the mixture, and then the melted mixture is heat-insulated to obtain the molten precursor.
[0014] Furthermore, the temperature after heating is 100-200°C; and the heat preservation treatment time is 5-10 minutes.
[0015] According to a second aspect of the present invention, an amorphous inorganic ion conductor is provided. The amorphous inorganic ion conductor is prepared by the method for preparing an amorphous inorganic ion conductor according to any one of the first aspects.
[0016] According to a third aspect of the present invention, there is provided a method for preparing a composite positive electrode for a solid-state lithium metal battery, comprising:
[0017] Lithium tetrachloroaluminate is coated on the positive electrode surface of the solid-state lithium metal battery and heat-treated to obtain a heat-treated positive electrode; sodium tetrachloroaluminate is coated on the positive electrode side of the solid electrolyte;
[0018] The solid electrolyte coated with sodium tetrachloroaluminate is covered on the surface of the heat-treated positive electrode, and the composite positive electrode is obtained after hot pressing and cooling and solidification; wherein, after the hot pressing and cooling and solidification, the lithium tetrachloroaluminate and the sodium tetrachloroaluminate in situ generate an amorphous inorganic ion conductor Li x Na 1-x AlCl4, 0.15≤x≤0.85.
[0019] Further, 0.55≤x≤0.85.
[0020] Further, x=0.55.
[0021] According to a fourth aspect of the present invention, a composite positive electrode for a solid-state lithium metal battery is provided, wherein the composite positive electrode is prepared by the composite positive electrode preparation method described in any one of the third aspects.
[0022] In general, the above technical solutions conceived by the present invention can achieve the following beneficial effects:
[0023] (1) In the present invention, lithium tetrachloroaluminate (LiAlCl4) and sodium tetrachloroaluminate (NaAlCl4) are uniformly mixed, melted to obtain a molten precursor, and then rapidly cooled to obtain an amorphous inorganic lithium ion conductor Li doped with LiAlCl4. x Na 1-x AlCl4 is used as the interface phase to inhibit the diffusion of elements between the positive electrode material and the solid electrolyte, which can improve the migration rate of lithium ions. Specifically, lithium tetrachloroaluminate is used as the main body and sodium tetrachloroaluminate is used as the dopant to prepare the amorphous inorganic lithium ion conductor Li x Na 1-x AlCl4 can achieve dual effects: on the one hand, it can induce eutectic (Li x Na 1-x AlCl4) forms anionic clusters Al n Cl 3n+1 - (n≥1) to increase the eutectic (Li x Na 1-x AlCl4) viscosity, hindering its crystallization at room temperature, thereby obtaining an amorphous structure to increase the system defect density and carrier concentration and promote ion migration; on the other hand, Na ions with large radius can broaden the bottleneck size of the ion migration path, reduce the ion migration energy barrier, increase ion conductivity, and thus improve the interface ion conductivity. Under the combined effect of these two aspects, the lithium ion migration rate can be greatly increased, the battery polarization can be reduced, and the rate performance can be improved.
[0024] Furthermore, the inorganic lithium ion conductor Li x Na 1-x AlCl4 has an amorphous structure. Compared with the existing method of introducing sintering aids as interface phases, it can significantly reduce the preparation temperature and further inhibit the element diffusion between the positive electrode material and the solid electrolyte.
[0025] (2) As a preferred embodiment, the amorphous inorganic lithium ion conductor Li x Na 1-xWhen the lithium content in AlCl4 is 0.55≤x≤0.85, within this content range, on the one hand, the eutectic temperature can be lowered at a higher eutectic ion conductivity, thereby reducing the element diffusion between the positive electrode material and the solid electrolyte; on the other hand, the oxidation voltage of the amorphous inorganic lithium ion conductor is higher, thereby improving the compatibility with high-voltage positive electrode materials.
[0026] (3) As a preferred embodiment, the amorphous inorganic lithium ion conductor Li x Na 1-x The lithium content in AlCl4 is x=0.55. At this content, the amorphous inorganic lithium ion conductor has the highest ionic conductivity and the highest oxidation voltage.
[0027] (4) Furthermore, by coating lithium tetrachloroaluminate (LiAlCl4) on the positive electrode surface of the solid-state lithium metal battery and performing heat treatment, the lithium tetrachloroaluminate can be melted and fill the positive electrode gap, and the lithium tetrachloroaluminate (LiAlCl4) and the sodium tetrachloroaluminate (NaAlCl4) coated on the positive electrode side of the solid electrolyte are in situ generated by hot pressing. Amorphous inorganic ion conductor Li x Na 1- x AlCl4, the amorphous inorganic ion conductor Li x Na 1-x AlCl4, as the interfacial phase for element diffusion between the positive electrode material and the solid electrolyte, can increase the migration rate of lithium ions.
[0028] In summary, the application of the binary system of lithium tetrachloroaluminate and sodium tetrachloroaluminate in the present invention can significantly reduce the preparation temperature and inhibit the element diffusion between the positive electrode material and the solid electrolyte; compared with other interface phases, the amorphous Li x Na 1-x The significant advantages of AlCl4 are low preparation temperature, controllable product crystal structure, high product ion conductivity, and good compatibility with solid electrolytes and positive electrode materials. The method of the present invention has a short preparation cycle, low cost, and is suitable for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Flow chart of the method for preparing an amorphous inorganic ion conductor in an embodiment of the present invention.
[0030] Figure 2 It is a schematic diagram comparing the interface ion transport characteristics, ion migration rate and depth characteristics, and interface stress / strain characteristics between the positive electrode material and the solid electrolyte when there is no amorphous inorganic ion conductor in the embodiment of the present invention and when there is an amorphous inorganic ion conductor in the embodiment of the present invention.
[0031] Figure 3 Li is obtained by mixing different molar ratios of lithium tetrachloroaluminate and sodium tetrachloroaluminate.x Na 1-x The ionic conductivity of AlCl4 varies with temperature.
[0032] Figure 4 is the Li prepared in the embodiment of the present invention 0.55 Na 0.45 SEM image of AlCl4.
[0033] Figure 5 Li-Ag|NI|LLZTO|Li assembled in the embodiment of the present invention x Na 1-x Cycling performance of AlCl4|LIC@LCO battery at 0.05C and 25℃.
[0034] Figure 6 Li-Ag|NI|LLZTO|Li at different rates in the embodiments of the present invention x Na 1-x Voltage curve of AlCl4|LIC@LCO. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0036] In the present invention, the terms "first", "second", etc. in the present invention and the accompanying drawings are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence.
[0037] like Figure 1 As shown, an embodiment of the present invention provides a method for preparing an amorphous inorganic ion conductor, wherein the amorphous inorganic ion conductor is used as an interface phase between a positive electrode material and a solid electrolyte of a solid-state lithium metal battery, and the preparation method comprises:
[0038] Mixing lithium tetrachloroaluminate (LiAlCl4) and sodium tetrachloroaluminate (NaAlCl4) uniformly to obtain a mixture;
[0039] The mixture is melted to obtain a molten precursor, and then rapidly cooled to room temperature to obtain an amorphous inorganic lithium ion conductor Li x Na 1-x AlCl4; wherein 0.15≤x≤0.85. x represents the amorphous inorganic lithium ion conductor Li x Na 1-x Lithium content in AlCl4.
[0040] Preferably, the molar ratio of sodium tetrachloroaluminate is 0.45-0.15, that is, 0.55≤x≤0.85. Within this content range, on the one hand, the eutectic temperature can be lowered at a higher eutectic ion conductivity, thereby reducing the element diffusion between the positive electrode material and the solid electrolyte; on the other hand, the oxidation voltage of the amorphous inorganic lithium ion conductor is higher, thereby improving the compatibility with the high-voltage positive electrode material.
[0041] Further preferably, the amorphous inorganic lithium ion conductor Li x Na 1-x The lithium content in AlCl4 is x=0.55. At this content, the amorphous inorganic lithium ion conductor has the highest ionic conductivity and the highest oxidation voltage.
[0042] In an embodiment of the present invention, the mixture is melted to obtain a molten precursor, comprising:
[0043] Under a protective atmosphere, the mixture is heated at a heating rate of 10 to 20°C / min to melt the mixture, and then the mixture is kept warm to obtain a molten precursor. Preferably, the protective atmosphere is argon. The temperature after heating can be 100 to 200°C, and the holding time can be 5 to 10 minutes, which can be adjusted according to actual conditions.
[0044] Preferably, when rapidly cooling to room temperature, the cooling rate is 10 to 50° C. / min.
[0045] In the embodiment of the present invention, an amorphous inorganic ion conductor Li x Na 1-x AlCl4; wherein 0.15≤x≤0.85; the amorphous inorganic ion conductor Li x Na 1-x AlCl4 is prepared by the above-mentioned method for preparing an amorphous inorganic ion conductor; the amorphous inorganic ion conductor is used as an interface phase between the positive electrode material and the solid electrolyte of a solid-state lithium metal battery.
[0046] In an embodiment of the present invention, a method for preparing a composite positive electrode for a solid-state lithium metal battery is also provided, comprising:
[0047] Lithium tetrachloroaluminate (LiAlCl4) is coated on the positive electrode surface of the solid-state lithium metal battery and heat-treated, so that the lithium tetrachloroaluminate can be melted and fill the positive electrode gap to obtain a heat-treated positive electrode; sodium tetrachloroaluminate (NaAlCl4) is coated on the positive electrode side of the solid electrolyte;
[0048] The solid electrolyte coated with sodium tetrachloroaluminate (NaAlCl4) is covered on the surface of the heat-treated positive electrode, and a composite positive electrode is obtained after hot pressing and rapid cooling and solidification; wherein, after hot pressing and rapid cooling and solidification, lithium tetrachloroaluminate and sodium tetrachloroaluminate in situ generate an amorphous inorganic ion conductor Li x Na 1-x AlCl4, 0.15≤x≤0.85.
[0049] Preferably, the temperature of heat treatment and hot pressing treatment is 100-200°C, the time of heat treatment is 5-10min, the heating rate during heat treatment is 10-20°C / min, and the cooling rate during rapid cooling is 10-50°C / min. In practical applications, adjustments are made according to specific circumstances.
[0050] In an embodiment of the present invention, a composite positive electrode for a solid-state lithium metal battery is also provided. The composite positive electrode is prepared by the above-mentioned method for preparing a composite positive electrode for a solid-state lithium metal battery.
[0051] In an embodiment of the present invention, a solid-state lithium metal battery is further provided, comprising a composite positive electrode, wherein the composite positive electrode is prepared by the above-mentioned composite positive electrode preparation method for a solid-state lithium metal battery.
[0052] In the present invention, lithium tetrachloroaluminate (LiAlCl4) and sodium tetrachloroaluminate (NaAlCl4) are uniformly mixed, melted to obtain a molten precursor, and then rapidly cooled to obtain an amorphous inorganic lithium ion conductor Li doped with LiAlCl4. x Na 1- x AlCl4 is used as the interface phase to inhibit the diffusion of elements between the positive electrode material and the solid electrolyte, which can improve the migration rate of lithium ions. Specifically, lithium tetrachloroaluminate is used as the main body and sodium tetrachloroaluminate is used as the dopant to prepare the amorphous inorganic lithium ion conductor Li x Na 1-x AlCl4 can achieve dual effects: on the one hand, it can induce eutectic (Li x Na 1-x AlCl4) forms anionic clusters Al n Cl 3n+1 - (n≥1) to increase the eutectic (Li x Na 1-xAlCl4) viscosity, hindering its crystallization at room temperature, thereby obtaining an amorphous structure to increase the system defect density and carrier concentration and promote ion migration; on the other hand, Na ions with large radius can broaden the bottleneck size of the ion migration path, reduce the ion migration energy barrier, increase ion conductivity, and thus improve the interface ion conductivity. Under the combined effect of these two aspects, the lithium ion migration rate can be greatly increased, the battery polarization can be reduced, and the rate performance can be improved.
[0053] Furthermore, the inorganic lithium ion conductor Li x Na 1-x AlCl4 has an amorphous structure. Compared with the existing method of introducing sintering aids as interface phases, it can significantly reduce the preparation temperature and further inhibit the element diffusion between the positive electrode material and the solid electrolyte.
[0054] The method for preparing the inorganic lithium ion conductor of the present invention has a short preparation cycle, low cost and is suitable for industrial application.
[0055] In the present invention, lithium tetrachloroaluminate (LiAlCl4) is coated on the positive electrode surface of the solid-state lithium metal battery and subjected to heat treatment, so that the lithium tetrachloroaluminate can be melted and fill the positive electrode gap, and the lithium tetrachloroaluminate (LiAlCl4) and sodium tetrachloroaluminate (NaAlCl4) coated on the positive electrode side of the solid electrolyte are in situ generated by hot pressing to form an amorphous inorganic ion conductor Li x Na 1-x AlCl4, the amorphous inorganic ion conductor Li x Na 1-x AlCl4, as the interfacial phase for element diffusion between the positive electrode material and the solid electrolyte, can increase the migration rate of lithium ions.
[0056] Figure 2 The interface ion transport characteristics, ion migration rate and depth characteristics, and interface stress / strain characteristics between the positive electrode material and the solid electrolyte are shown without and with the amorphous inorganic ion conductor of the present invention. Without the amorphous inorganic ion conductor of the present invention, the interface ion transport is uneven, the ion migration rate and depth are low, and the interface stress / strain is large; with the amorphous inorganic ion conductor of the present invention, the interface ion transport is uniform, the ion migration rate and depth can be improved, and the interface stress / strain can be relieved.
[0057] The method of the present invention is further described below with reference to specific embodiments.
[0058] Lithium tetrachloroaluminate and sodium tetrachloroaluminate were prepared in a molar ratio of 0.15:0.85, 0.25:0.75, 0.35:0.65, 0.45:0.55, 0.55:0.45, 0.65:0.35, 0.75:0.25, 0.85:0.15, and ground in a mortar to mix the two compounds evenly. The mixture was placed in a stainless steel crucible, heated to 160°C at a rate of 10°C / min under an argon environment, and kept at 160°C for 10 minutes to obtain a molten precursor; then cooled to room temperature at a cooling rate of 20°C / min to obtain the corresponding amorphous Li x Na 1-x AlCl4 inorganic electrolyte material; in other embodiments, the heating rate can also be 12°C / min, 15°C / min, 20°C / min, etc., the temperature after heating can also be 100°C, 130°C, 200°C, etc., the insulation time can also be 5min, 7min, etc., and the cooling rate can also be 10°C / min, 30°C / min, 50°C / min, etc.
[0059] 50 mg of lithium cobalt oxide (LiCoO2, LCO), Li3InCl6, LiAlCl4, PVDF binder and indium tin oxide (In2O5Sn, ITO) with a mass ratio of 60:20:15:3:2 were ground and mixed in a mortar, and then 200 μl of toluene was added and stirred at 500 rpm to prepare an active material suspension. 10 μl of the suspension was drop-casted on the surface of a carbon-coated aluminum foil with a diameter of 8 mm. After the solvent evaporated, the electrode was cold-pressed at 200 MPa for 1 min to prepare a positive electrode. In other embodiments, other commonly used positive electrode materials can also be used to prepare positive electrode sheets.
[0060] Subsequently, 10 μl of LiAlCl4 suspension (40 mg LiAlCl4 / 200 μl n-heptane) is dripped onto the surface of the positive electrode sheet and heated to 160°C to melt the LiAlCl4 and fill the positive electrode pores. In other embodiments, 100°C, 120°C, 200°C may also be used, the heating time may be 5 min, 7 min, 10 min, etc., and the heating rate may be 10°C / min, 12°C / min, 20°C / min, etc.
[0061] Finally, in Li 6.4 LqCy 1.4 Ta 0.6 O 12 / (solid electrolyte) coated on the positive electrode side x Na 1-x AlCl4 molten salt, or in Li 6.4 LqCy 1.4 Ta 0.6 O 12 / The positive electrode side of the battery is coated with NaAlCl4 and covered on the surface of the positive electrode plate. The battery is hot pressed at 180°C for 5 minutes, and then rapidly cooled and solidified to obtain a composite positive electrode. Metal lithium is used as the negative electrode to assemble into an all-solid-state lithium metal battery.
[0062] Figure 3 Li is obtained by mixing different lithium tetrachloroaluminate and sodium tetrachloroaluminate in molar ratio in the above embodiment. x Na 1-x The ionic conductivity of pure LiAlCl4 and NaAlCl4 before and after heat treatment varies with temperature. Pure LiAlCl4 and NaAlCl4 are used as comparative examples. It can be seen that even after the same heat treatment process, the ionic conductivity of pure LiAlCl4 and NaAlCl4 as comparative examples at different temperatures is significantly lower than that of LiAlCl4 at different ratios in the embodiment of the present invention. x Na 1- x AlCl4, indicating that the doping effect significantly improves the ionic conductivity.
[0063] Figure 4 is the Li prepared in the embodiment of the present invention 0.55 Na 0.45 SEM image of AlCl4 shows that at this ratio, Li 0.55 Na 0.45 AlCl4 presents a bulk morphology, in which a large number of polyhedral crystalline particles with nanometer size are embedded in the bulk matrix. The embedded nanoparticles may be LiCl crystals precipitated during the eutectic process, while the bulk matrix deforms under electron beam irradiation, indicating that it has an amorphous structure.
[0064] Figure 5 Li-Ag|NI|LLZTO|Li assembled in the embodiment of the present invention x Na 1-x AlCl4|LIC@LCO (where x=0.55) and comparative example Li-Ag|NI|LLZTO|LiAlCl4|LIC@LCO battery cycling performance at 0.05C and 25°C, where the negative electrode side is modified with AgNO3 to form a lithium-silver alloy negative electrode (Li-Ag) and a nitride interface phase (NI), the positive electrode side solid electrolyte is Li3InCl6 (LIC), and the positive electrode material is LiCoO2 (LCO). It can be seen that compared with the LiAlCl4 interface phase, Li x Na 1-x AlCl4 significantly improves the discharge capacity and cycle stability of the battery. It should be noted that in other embodiments, similar curves are obtained when x is between 0.15 and 0.85.
[0065] Figure 6 Li-Ag|NI|LLZTO|Li at different rates in the embodiments of the present invention x Na 1-x Voltage curve of AlCl4|LIC@LCO battery, where x=0.55; it can be seen that even at a high rate (0.5C), the battery of the embodiment of the present invention can still operate normally and maintain a stable electrochemical curve. When the rate returns to 0.1C, the capacity can be reversibly restored. In other embodiments, x is 0.15 to 0.85 and there are similar curves.
[0066] Experiments have shown that the amorphous inorganic lithium ion conductor Li prepared in the present invention x Na 1-x AlCl4 acts as an interfacial phase to inhibit the diffusion of elements between the positive electrode material and the solid electrolyte. The ionic conductivity of the amorphous inorganic lithium ion conductor can reach 4-5×10 -5 S cm -1 , the battery rate performance reaches 0.5C.
[0067] In summary, the present invention can synthesize a novel nanostructured carbon nanotube with low melting point and high ionic conductivity (4-5×10 -5 S cm -1 ) and viscoelastic Li x Na 1-x AlCl4, as the interfacial phase between the positive electrode material and the solid electrolyte, can increase the interfacial ion conduction rate, reduce battery polarization and improve rate performance; it can also construct an efficient lithium ion percolation network, effectively increase the uniformity of interfacial ion transmission, improve the ion migration rate and depth, and relieve electrode stress / strain.
[0068] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an amorphous inorganic ion conductor, characterized in that: include: Mixing lithium tetrachloroaluminate and sodium tetrachloroaluminate uniformly to obtain a mixture; The mixture is melted to obtain a molten precursor, and after cooling to room temperature, an amorphous inorganic lithium ion conductor Li x Na 1-x AlCl4, 0.15≤x≤0.85; Wherein, the amorphous inorganic lithium ion conductor Li x Na 1-x AlCl4 is used as the interfacial phase between the positive electrode and the solid electrolyte in solid-state lithium metal batteries.
2. The method for preparing an amorphous inorganic ion conductor according to claim 1, characterized in that: 0.55≤x≤0.85。 3. The method for preparing an amorphous inorganic ion conductor according to claim 2, characterized in that: x=0.55。 4. The method for preparing an amorphous inorganic ion conductor according to claim 1, characterized in that: Melting the mixture to obtain a molten precursor comprises: Under a protective atmosphere, the mixture is heated at a heating rate of 10 to 20° C. / min to melt the mixture, and then the melted mixture is heat-insulated to obtain the molten precursor.
5. The method for preparing an amorphous inorganic ion conductor according to claim 4, characterized in that: The temperature after heating is 100-200°C; the insulation treatment time is 5-10 minutes.
6. An amorphous inorganic ion conductor, characterized in that: The amorphous inorganic ion conductor is prepared by the method for preparing an amorphous inorganic ion conductor according to any one of claims 1 to 5.
7. A method for preparing a composite positive electrode for a solid-state lithium metal battery, characterized in that: include: Lithium tetrachloroaluminate is coated on the surface of the positive electrode of the solid-state lithium metal battery and heat-treated to obtain a heat-treated positive electrode; Sodium tetrachloroaluminate is coated on the positive electrode side of the solid electrolyte; The solid electrolyte coated with sodium tetrachloroaluminate is covered on the surface of the heat-treated positive electrode, and the composite positive electrode is obtained after hot pressing and cooling and solidification; wherein, after the hot pressing and cooling and solidification, the lithium tetrachloroaluminate and the sodium tetrachloroaluminate in situ generate an amorphous inorganic ion conductor Li x Na 1-x AlCl4, 0.15≤x≤0.
85.
8. The method for preparing a composite positive electrode according to claim 7, characterized in that: 0.55≤x≤0.85。 9. The method for preparing a composite positive electrode according to claim 8, characterized in that: x=0.55。 10. A composite positive electrode for a solid-state lithium metal battery, characterized in that: The composite positive electrode is prepared by the composite positive electrode preparation method according to any one of claims 7 to 9.
Citation Information
Cited By
Lithium ferrite lithium supplement agent and preparation method and application thereof
CN119447310A